1997
DOI: 10.1099/00221287-143-8-2639
|View full text |Cite
|
Sign up to set email alerts
|

The form of folate affects the mechanisms of methotrexate resistance in Enterococcus faecium

Abstract: Several mechanisms have been described to explain the resistance of cells to methotrexate (MTX); however, the basis for the heterogeneity of mechanisms has been obscure. It was hypothesized that the type of MTX resistance in a single species can be influenced by the form of extracellular folate supplied during the development of resistance. Two strains of MTX-resistant Enterococcus faecium were developed by transferring the bacteria to media containing increasing concentrations of MTX in the presence of consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…There have been at least 2 known changes that could contribute to these effects: the properties of the microorganism could have been slightly changed in the process of rendering it antibiotic resistant and subculturing the wild-type microorganism in L2 over the last 40 y could have changed its properties. Tamura et al (18) have shown that the form of folate used during the development of methotrexate resistance affects the response of the assay organism to folates. A similar phenomenon could have occurred with the chloramphenicol-resistant microorganism, making it respond slightly better to reduced folates.…”
Section: Discussionmentioning
confidence: 99%
“…There have been at least 2 known changes that could contribute to these effects: the properties of the microorganism could have been slightly changed in the process of rendering it antibiotic resistant and subculturing the wild-type microorganism in L2 over the last 40 y could have changed its properties. Tamura et al (18) have shown that the form of folate used during the development of methotrexate resistance affects the response of the assay organism to folates. A similar phenomenon could have occurred with the chloramphenicol-resistant microorganism, making it respond slightly better to reduced folates.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Although pABA can cross membranes by simple diffusion (18), folate and pteridine fluxes are likely to be carrier-mediated, as in animals (19 -22) and bacteria (23)(24)(25). Plants, therefore, presumably have several as yet undiscovered organellar folate or pteridine transporters (Fig.…”
mentioning
confidence: 99%
“…Prolonged exposure of target cells to folate antagonists such as methotrexate and trimethoprim might result in resistance. In cancer cells, several mechanisms were described such as: reduction of the folylpolyglutamate synthetase activity, amplification of the gene coding for DHFR or a decrease in the binding affinity for methotrexate on the DHFR (Tamura et al, 1997). However, to date, folate overproduction has not been considered or described as a mode of resistance against methotrexate.…”
Section: Introductionmentioning
confidence: 99%